The Smart Aquaponic System Integrated with Internet of Things Technology - Mohd Nor, Muhammad Aiman; Puteh, Saifullizam (Emerging Advances in Integrated Technology, 2025)
Aquaponics is a sustainable plant method that combines aquaculture (fish life) and hydroponics (soilless plants) in a closed cycle. To achieve optimal results, aquaponics requires a robust water cycle and meticulous maintenance, including monitoring temperature, environmental air humidity, and plant media humidity, among other factors. The current aquaponics system still relies on manual methods for monitoring, lacking an integrated system to handle this care function. Therefore, we developed this product to address these issues by concentrating on creating intelligent aquaponic systems that integrate the Internet of Things, enabling users to track necessary parameters. Additionally, the system automates tasks like irrigation and fish feeding schedules. In this development, the researcher employed the 7-phase Engineering Design Process (EDP) model, which includes the following stages: (1) defining the problem, (2) conducting research, (3) developing a solution concept, (4) constructing a prototype, (5) constructing a product, (6) conducting a product analysis, and (7) improving the product. he BBC micro:bit microcontroller as the main controller and the ESP01s WiFi module as the component that allows interaction with ThingSpeak. Next, the researcher used several types of sensors, such as DHT11, HC-SR04, capacitive soil moisture sensor v1.2, DS18B20, and actuators such as a DC water pump motor and a FS90 180-degree servo motor. As a result, the researcher successfully met the set objectives, including the design, development, and testing of the product's functionality, and the product performed as expected. Finally, according to experts, this product's weakness is that it requires the addition of a humidity sensor installed on each plant pot, which is recommended for further study due to limitations on the microcontroller's I/O pins.